International law and the use of force : cases and materials - Janik, Ralph (New York : Routledge, 2020)
"This book introduces key issues on the use of force, while also providing a detailed analysis of technological developments and recent legal discussions in the field. The author examines areas such as drone warfare, the concept of humanitarian intervention, the Responsibility to Protect, and recent conversations around the fight against the Islamic State in a clear and accessible manner, through a thorough presentation of relevant cases and materials. This book is essential reading for students studying force and its intersection with international law"--
OCLC-licensed vendor bibliographic record.
Keywords: War (International law); Humanitarian intervention; Responsibility to protect (International law); LAW / General